Odpowiedzi

2009-10-31T16:59:17+01:00
A) 5¹/₁₂-(4³/₈-⁵/₁₂):3⁹/₁₆ = 61/12-(35/8-5/12):57/16 = 61/12-(105/24-10/24)*16/57 = 61/12-95/24*16/57 = 61/12-190/171 = 10431/2052-2280/2052=8151/2052=3 i 1995/2052 = 3 i 665/684

b) (5¹/₆+12⁵/₈)-2¹/₁₂*2⁷/₁₀=(31/6+101/8)-25/12*27/10 = (124/24+303/24)-45/8 = 427/24-45/8 = 427/24-135/24= 292/24 = 12 4/24= 12⅙

c)1⁵/₆+43₁/²:(4-1³/₄)=11/6+87/2:(2¼) = 11/6+87/2*4/9 = 11/6+58/3 = 11/6+116/6 = 127/6 = 21⅙

d)1 ⁴/₁₁*1⁵/₆+(5⁵/₆+2³/₈)= 15/11*11/6+(35/6+19/8) = 5/2+(140/24+57/24) = 5/2+197/24 = 60/24+197/24 = 257/24 = 10 i 17/24

e)3³/₄+(10²/₇-1¹/₂):1²⁰/₂₁=15/4+(72/7-3/2):41/21 = 15/4+(144/14-21/14)*21/41 = 15/4+123/14*21/41 = 15/4+9/2 = 15/4+18/4=33/4=8 ¼